Pengelolaan Piutang Pola Channeling Melalui Penyesuaian Sistem Akuntansi Pada Koperasi - Theofanny, Gracia; Sugiyanto, Sugiyanto; Dewi Sumaryana, Fitriana (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
The KSP Sumber Makmur Karyawan’s Balance Sheet Report shows 70% of the total cooperative assets in the form of account receivables, if further analysis shows that the distribution of loans in the Cooperative comes from its own capital and also loan capital through channeling pattern, at KSP Sumber Makmur Karyawan one of them with a channeling pattern receivable accounting system. This pattern involves a third party, namely the Bank for financing loans to members. This study aims to analyze the management of account receivables from loan capital adjusted to the accounting system in order to produce appropriate financial information. The research method used a qualitative approach with a case study method, the data used is primary data and secondary data, with data analysis techniques in the form of interview, observation, and literature study. The results of the study explain that KSP Sumber Makmur Karyawan has implemented an accounts receivable accounting system, but there are several shortcomings of the system, the first is the problem of procedures between loan applications and approvals, and installment payments are still put together, and the last is the separation of functions between administrative functions and cash functions there is still no separation.